The combined influence of hydrophobicity, charge and molecular weight on natural organic matter removal by ion exchange and coagulation - Finkbeiner, Pascal; Moore, Graeme; Pereira, Ryan; Jefferson, Bruce; Jarvis, Peter (Elsevier, 2019)
Three different source waters were investigated using virgin and pre-used anion exchange resins, coagulation, and ion exchange combined with coagulation (IEX&Coagulation). The hydrophobicity, size distribution and charge of natural organic matter (NOM) were used to evaluate its removal. Dissolved organic carbon (DOC) removal by pre-used IEX resin was 67–79%. A consistent ratio of different hydrophobicity fractions was found in the removed DOC, while the proportion and quantity of the molecular weight fraction around 1 kDa was important in understanding the treatability of water. For pre-used resin, organic compounds were hypothesised to be restricted to easily accessible exchange sites. Comparatively, virgin resin achieved higher DOC removals (86–89%) as resin fouling was absent. Charge density and the proportion of the hydrophobic fraction were found to be important indicators for the specific disinfection byproduct formation potential (DBP-FP). Treatment of raw water with pre-used resin decreased the specific DBP-FP by between 2 and 43%, while the use of virgin resin resulted in a reduction of between 31 and 63%. The highest water quality was achieved when the combination of IEX and coagulation was used, reducing DOC and the specific DBP-FP well below that seen for either process alone.
Keywords: ion exchange; charge density; natural organic matter; disinfection byproducts